BRITISH COLONIAL RULE AND THE DEVELOPMENT OF SMALLHOLDER COCOA PLANTATION IN SOUTHWESTERN NIGERIA, 1900-1945 - Adesola Adesote (مجلة اداب ذي قار, 2025)
This paper critically examines the influence of British colonial rule on the development of smallholder cocoa plantation in Southwestern Nigeria between 1900 and 1945. The period between 1900 and 1945 was characterised by the growth of cash economy and had its foundation in the development of agricultural export products called ‘’cash crops”. It focuses on the influence of the British colonial agricultural policies on the development of smallholder cocoa plantation in Southwestern Nigeria. Up to 1945, cocoa plantation was solely in the hands of peasant farmers in the region. Virtually all the cocoa farms set up in different parts of Southwestern Nigeria during this period were owned by individuals. However in the post-1945, the government, most especially the Western Regional Government became involved in plantation agriculture resulting in the emergence of government-owned plantations. The methodological approach adopted in this paper is historical, thematic, qualitative and quantitative. Sources of information include primary and secondary materials derived from archives, oral interviews and extant literature.